2018
DOI: 10.1080/15582159.2018.1442087
|View full text |Cite
|
Sign up to set email alerts
|

Parental preferences in the choice for a specialty school

Abstract: Choosing a specialty school involves huge challenges for families. This research aims to understand the behavioral process that leads families to choose among various specialty school programs. Discrete choice models, based on revealed preferences data from middle school applications in a large school district in Florida, are estimated using both, the top and all-ranked alternatives. This study returns insights into geographic settings, theme specialties and socioeconomic characteristics of applicants, schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 60 publications
(72 reference statements)
2
4
0
1
Order By: Relevance
“…issues (commuting problems) could be an important factor in this subset of revised school choices. This is in line with the observation that school proximity to place of residence is very important across different social groups in Czechia and other countries (Meyer & Kučerová, 2018;Müller et al, 2012;Prieto et al, 2018;Simonová, 2017). On the other hand, changing school without changing field of study had different effects.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…issues (commuting problems) could be an important factor in this subset of revised school choices. This is in line with the observation that school proximity to place of residence is very important across different social groups in Czechia and other countries (Meyer & Kučerová, 2018;Müller et al, 2012;Prieto et al, 2018;Simonová, 2017). On the other hand, changing school without changing field of study had different effects.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the spatial factors, the assumption that school specialisation and distance are substitutes (Müller et al, 2012;Prieto et al, 2018) is supported by our data on home-to-school distance for general academic and vocational schools. 2 However, the finding that transfers within each tier are associated with shorter school distances can be explained by different mechanisms (Bertrand-Cloodt et al, 2010) and further detailed analysis is needed to better understand this result.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Better-educated parents make better-informed choices [63]. Previous studies have found that applicants take into consideration their social circumstances when stating their preferences for specialty schools [74]. SDHC does not have poverty level or race/ethnicity in the criteria for admission, yet both the criteria at the time of the decision on admission show relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Alanyazına göre, ebeveynlerin çocuklarının gitmesini istedikleri okula ilişkin (devlet veya özel) tercihlerinde temel belirleyicilerden biri akademik kalitedir (Altenhofen, Berends ve White, 2016;Beavis, 2004;Figlio ve Stone, 2001;Härmä, 2013;Hausman ve Goldring, 2000;Heyneman ve Stern, 2014;Prieto, Aguero-Valverde, Zarrate-Cardenas ve Maarseveen, 2019;Stewart ve Wolf, 2014). Ebeveynlerin başarılı okulları seçme olasılıkları daha yüksektir (Hastings ve Weinstein, 2008;Kisida ve Wolf, 2010).…”
Section: Introductionunclassified